MAQASHID SYARIAH DAN TANTANGAN DEKADENSI MORAL DALAM PERSPEKTIF ESKATOLOGI ISLAM - Ilmi, Iqbal; Syafa’ah, Livia; Pratiwi, Bintang (Mitsaqan Ghalizan, 2025)
The decline of ethics and morality in modern society is considered one of the minor signs of the apocalypse (qiyamat sugra) in Islamic teachings. This study aims to analyze this phenomenon from the perspective of the Qur'an and Hadith, as well as to examine its underlying causes and impacts on social life. Additionally, the study explores the eschatological aspect of Islam, emphasizing that moral decay is part of the signs of the end times. The research employs a qualitative method with a library research approach, in which data is gathered from religious texts, books, journal articles, and previous studies. The findings indicate that signs of the apocalypse related to morality include the decline of religious knowledge, increasing ignorance, open engagement in immoral acts such as fornication, and social imbalance. These conditions are further worsened by the influence of globalization, the rapid advancement of technology without moral oversight, and the lack of character education within families and schools. Moreover, the failure to apply the principles of Maqashid Syariah, such as the protection of religion (hifz al-diin), life (hifz al-nafs), intellect (hifz al-‘aql), and lineage (hifz al-nasl), has become a fundamental factor contributing to the erosion of moral values in society. The consequences of this moral decline include social disintegration, rising crime rates, and the loss of ethics and mutual respect, especially among the younger generation